DINAMIKA KARBON DAN AKTIVITAS β-GLUKOSIDASE DI TOPSOIL DAN SUBSOIL LAHAN PERTANIAN MONOKULTUR NAGARI ALAHAN PANJANG SUMATERA BARAT - Sri Dewi Murni; Agustian Agustian; Mimien Harianti (Jurnal Tanah dan Sumberdaya Lahan, 2023)
This study aimed to determine the dynamics of carbon and glucosidase enzyme activity in the topsoil and subsoil of monoculture land. This research was in Nagari Alahan Panjang, West Sumatra. Soil samples were taken using a purposive random sampling method on three cropping patterns: monoculture, rotation and intercropping, and two depths of 0-15 cm and 15-30 cm. The parameters analyzed included total N, organic C, exchangeable K, Ca, Mg, and Na, glucosidase, biomass C, and respiration. Data from observations were analyzed with Pearson statistics 8 correlation. The results showed that β-glucosidase activity was positively correlated with total N and organic C, biomass C was positively correlated with exchangeable Mg, and respiration was positively correlated with N total and β-glucosidase.